Development of comics-based learning media on motion and force material to improve learning motivation of Junior High School students - Meyta Hosana; Mella Mutika Sari; Ratna Yulinda (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
The rapid changes of the 21st century require educators to adapt and create a creative learning process to enhance motivation in learning and produce high-quality students. However, it has been observed that some students struggle with focus as they become distracted by other activities such as playing or chatting, leading to difficulties in completing assignments, especially in subjects that involve calculations. This study aims to assess the validity, practicality, and effectiveness of instructional media in increasing the learning motivation of junior high school students. The development model applied is ADDIE (Analysis, Design, Development, Implementation, and Evaluation), with validation conducted through validation sheets, practicality assessed using student response questionnaires, and effectiveness measured through learning outcome tests. Validation results from three experts indicated a validity level of 89% (Very Valid), while practicality testing through student response questionnaires reached 84% (Very Practical). The effectiveness test showed an average score of 69, with an N-gain score of 0.6257 (Moderate) and an N-gain percentage of 62.5733 (Effective). Based on the research findings, comic-based learning media for the Motion and Force has been proven to be valid, practical, and effective in enhancing student motivation in junior high school learning.